Barriers and facilitators for adopting a healthy lifestyle in a multi-ethnic population: A qualitative study - Subramaniam, Mythily; Devi, Fiona; AshaRani, P. V.; Zhang, Yunjue; Wang, Peizhi; Jeyagurunathan, Anitha; Roystonn, Kumarasan; Vaingankar, Janhavi Ajit; Chong, Siow Ann (PloS one, 2022)
A healthy lifestyle is defined as ‘a way of living that lowers the risk of being seriously ill or dying early.’ Although barriers and facilitators of healthy lifestyles have been well-studied among populations like those with chronic non-communicable diseases, adolescents, and older adults in Asia, less information is available on barriers and facilitators perceived by the general adult population. Using a qualitative methodology and leveraging the socio-ecological model, the current study aimed to understand the barriers and facilitators of a healthy lifestyle in a sample of Singapore residents. Overall, 30 semi-structured interviews were conducted in English and other local languages from August 2020 to March 2021. Transcripts were analysed using framework analysis. Five main themes pertaining to personal, interpersonal, environmental, socio-cultural, and policy-level factors were classified under the two overarching categories of barriers and facilitators of healthy lifestyles. The results of this study offer important insights into understanding the barriers and facilitators to the adoption of a healthy lifestyle among people in Singapore. Furthermore, our findings illustrate the complex interplay between individuals, social relationships, environment, and policy that can act as either a barrier or a facilitator to adopting a healthy lifestyle.